The landscape of preventive cardiology in Turkey: Challenges and successes - Lale Tokgozoglu; Meral Kayikcioglu; Banu Ekinci (Elsevier, 2021)
Turkey, like many countries, is facing a growing burden of non-communicable disease (NCD)s and is among the countries with high cardiovascular mortality in Europe. Moreover, Turkey currently has the highest rate of premature cardiovascular disease (CVD) in Europe. During the last decades, Turkey made fundamental reforms in the health system to improve the treatment of risk factors to prevent CVD. The most outstanding success was in the area of tobacco control (13.4% decrease in smoking prevalence) and decreasing the salt consumption of the population (from 18 to 9.9 g/day) leading to a significant decrease in CVD mortality from 45% to 36.8% of all deaths. However, obesity and diabetes are increasing rapidly as a result of urbanization, low physical activity and unhealthy eating and the new generation is starting to take up smoking. The increase in cardiometabolic risk factors and aging of the population are expected to increase the number of CVD deaths. All CVD risk factors except smoking are significantly more prevalent in women. In addition, rare disease is a country specific problem with a significant contribution to the high rates of premature CVD in Turkey. Despite major improvements in management in acute coronary syndromes, sustained achievement in guideline recommended goals is suboptimal. In patients with a previous cardiovascular event smoking rate is 25.5%, 80.9% of these patients are overweight (BMI ≥25 kg/m2), 30% obese (BMI ≥30 kg/m2), and LDL‐cholesterol targets of 70 mg/dL are attained in only 18%. Herein, we scrutinize the achievements and challenges of Turkey in establishing a 'National Heart Health Policy' aiming to decrease the burden of CVD and its risk factors.